A Rare Form of Silene acaulis L. (moss Campion) from British Columbia - Revel, Richard D. (ARCTIC, 1980)
While conducting an Ecological Reserves survey of Morfee Mountain in North Central British Columbia (55° 26' N, 123° 04' W) during mid-July 1971, the author noted an interesting variation of flower colour in Silene acaulis L. subsp. subacaulescens (F.N. Williams) Hult. The flower colours of Silene acaulis are usually purple, pink or lavender throughout its range. The majority of the individuals of this species on Morfee Mountain conformed to the usual flower colour. However, one individual plant with pure white petals was observed . The specimen was collected near the British Columbia Telephone Company microwave relay station on Morfee Mountain at an elevation of about 1700 m. . Although the white-flowered form of Silene acaulis is not unknown, Hultén (1968) notes that this form is rare, thus making the find an interesting observation for both the amateur botanist and the more serious student of intraspecific variation in plants.